Faktor-Faktor yang Berhubungan dengan Pernikahan Dini pada Wanita - Kanella Ayu Wulanuari; Anggi Napida Anggraini; Suparman Suparman (Alma Ata University Press, 2017)
A study by UNICEF in Indonesia find that the number of early marriage for 15 years old is 11% and 18 years is 35%. Generally, early marriage is more common in women than men, it’s approximately 5% of boys get married before they are 19 years old. The purpose of this study was to determine factors relating to early marriage in women and the most significant factor relating to early marriage. The study used observational quantitative study with case-control study design. The population of the study was 132 married women, samples were selected by using total sampling technique with the inclusion and exclusion criteria. The respondents of this study were 53 women. Data were analysis by chi square test and logistic regression. The results of chi-square test showed variables that had relationship with early marriage were respondents' education (p=0.035), respondents’ income (p=0.000), and sexual pre marriage (p=0.006) whereas variables that did not have relationship with early marriage are father's education (p=0.436), mother’s education (p=0.290), parents’ income (p=0.356) and respondents’ religiosity (p=0.489). The result of logistic regression analysis showed that respondents’ income was the most dominant factor affecting early marriage in women. Conclusion the most significant factor related to early marriage was respondents’ income.